Treatment Using the Method of Laser Therapy in Dentistry - Valijonovna, Orifkhujaeva Mekhriniso (American Journal of Bioscience and Clinical Integrity, 2024)
Laser systems used for the treatment of caries affect the hard and soft tissues of the teeth. The ability to adjust the power and wavelength allows the installation to be used in different clinical situations. Laser radiation is absorbed and reflected by the tissues it affects. When using a laser to treat caries, the absorber is water. The effect carried out is absolutely safe for humans. In order to cure caries,it is necessary: carefully treat, remove the decaying tooth tissues affected by bacteria, ensure the sterility of the treated surface and install a seal in place of the carious cavity.